Geochemical characterization of natural gases in the pre-salt section of the Santos Basin (Brazil) focused on hydrocarbons and volatile organic sulfur compounds. (October 2022) - Souza, Igor V.A.F.; Ellis, Geoffrey S.; Ferreira, Alexandre A.; Guzzo, Jarbas V.P.; Díaz, Rut A.; Albuquerque, Ana Luiza S.; Amrani, Alon
Abstract: The objective of this work is to characterize the geochemistry of a suite of natural gas samples from five fields in order to improve the understanding of the lacustrine petroleum system of the pre-salt section from the Santos Basin (Brazil). Additionally, the distribution of volatile organic sulfur compounds (VOSC) in petroleum reservoirs was examined to investigate possible applications to petroleum systems assessments. The hydrocarbon gases were generated by thermogenic processes associated with the oil window. The 13 C-enriched values for C1 (>−40‰) were interpreted as an organic source signature rather than an indication of thermal maturity, except for the oil occurrence (Field B), where a different fluid charge mainly composed of methane and CO2 from a minor external kitchen area in the Santos Basin was identified. The molecular composition and the carbon and hydrogen isotopic data of the hydrocarbon gases, when combined with the VOSC molecular compositional data, allow the identification of four gas families associated with different kitchens and/or migrations pathways. The total VOSC concentrations range from 0.7 to 23.9 ppm by volume (ppmV). The organic sulfides are mainly composed of carbonyl sulfide (COS) and diethyl sulfide. The main thiol compound is ethanethiol. The cyclic VOSC are primarily composed of thiophene, with a negligible amount of branched thiophenes (<0.1 ppmV). H2 S showed a strong positive Pearson's correlation with COS and methanethiol (MeSH) concentrations (r = 0.943 and 0.807, respectively). This suggests that COS and MeSH formation was linked to H2 S generation and/or post-catagenetic interactions between hydrocarbons and H2 S, mainly related to thermochemical sulfate reduction (TSR). In contrast, the distribution of higher molecular weight VOSC seems to be controlled by source rock facies, rather than H2 S concentration. Principal component analysis of the VOSC compositional data identified some subgroups within the gas families mainly associated with TSR. The results presented in this work reveal that VOSC can be an important auxiliary tool in petroleum system studies. Highlights: Four gas families were identified in pre-salt reservoirs. Detailed description of volatile organic sulfur compounds in geological reservoirs. Organic sulfur distribution supported the distinction of the gas families. Carbonyl Sulfide as a proxy for recent thermochemical sulfate reduction.